INFLUENCE OF STOCK MARKET SIZE ON THE GROWTH OF CORPORATE BOND MARKET IN KENYA - Wanyama, Dr. David W. (International Journal of Finance, 2017)
Purpose: The purpose of this study was to analyze how stock market size influences the growth of corporate bond market in Kenya. Methodology: The study used descriptive and causal research designs. Secondary data was used. The sample of the study consisted of daily and monthly time series covering six years beginning January 2009 to December 2014. Unit root tests using Augmented Dickey-Fuller (ADF) and Phillips-Perron tests were done. The study used Eviews econometric software to facilitate empirical analysis of data. Results: Regression of coefficients results shows that Stock market size and corporate bonds are positively and significant related (r=0.029, p=0.002). The results revealed that stock market capitalization does not granger cause corporate bond market in Kenya. Unique Contribution to Theory, Practice and Policy: This study recommends for Policy makers in Kenya to find ways and means of increasing the size of the stock market to reap the aforementioned benefits. A large size of the stock market will cause the benefits to flow to the corporate bond market too.